Review and Hypothesis. New insights into the reaction mechanism of transhydrogenase: Swivelling the dIII component may gate the proton channel. Issue 16 (2nd July 2015) - Jackson, J. Baz; Leung, Josephine H.; Stout, Charles D.; Schurig-Briccio, Lici A.; Gennis, Robert B.
Abstract : The membrane protein transhydrogenase in animal mitochondria and bacteria couples reduction of NADP + by NADH to proton translocation. Recent X‐ray data on Thermus thermophilus transhydrogenase indicate a significant difference in the orientations of the two dIII components of the enzyme dimer (Leung et al., 2015). The character of the orientation change, and a review of information on the kinetics and thermodynamics of transhydrogenase, indicate that dIII swivelling might assist in the control of proton gating by the redox state of bound NADP + /NADPH during enzyme turnover.